Development of Mucoadhesive Gel Microbicide to Target Mucosal HIV Reservoirs - Ranjita Shegokar; Kamalinder K Singh (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2014)
The wide use of microbicide is mainly depends on its effectiveness, less frequent application, ready availability and most importantly cost. The aim of this work was to develop affordable microbicide mucoadhesive gel formulation of synthetic anti HIV drug, stavudine and to characterise it in terms of its physical properties, mucoadhesiveness and spreadability. The purpose of the present study was also to compare different dissolution media used for in vitro release of vaginal dosage form. The gels were tested for antimicrobial, spermicidal and anti-HIV activity. Gels prepared using Carbopols and Polycarbophil were transparent and homogenous and had excellent mucoadhesion index - and showed fast drug release profile. Gels showed very good antimicrobial action against pathological microorganism.